Bens Radio 106.2 FM Jakarta Strategy in Building Relations With Listeners - Yayu Sriwartini; Gita Safitri (IJESS International Journal of Education and Social Science, 2022)
The purpose of this study was to describe the communication strategy of Bensr Radio 106.2 FM Jakarta in building relationships with listeners. The theory used is relationship management theory and social exchange theory. The research approach is qualitative with in-depth interview data collection techniques and literature review of digital documentation. There are 3 resource persons consisting of station managers, broadcasters and listeners. The validity of the data was tested by using triangulation of sources and methods. The results of the study illustrate that there are four strategies carried out in fostering relationships with listeners, namely creating fan clubs through social media Facebook, Instagram and YouTube, holding special events, organizing birthday events regularly and maintaining intimacy through broadcaster communication styles and methods.